2019
DOI: 10.3390/nu11081931
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-Term Omega 3 Polyunsaturated Fatty Acid Supplementation with or without Multidomain Lifestyle Intervention on Muscle Strength in Older Adults: Secondary Analysis of the Multidomain Alzheimer Preventive Trial (MAPT)

Abstract: Background: The benefits of long-term omega 3 polyunsaturated fatty acid (ω3-PUFA) supplementation on muscle strength in older adults remains to be investigated. Objectives: We assessed the effect of ω3-PUFA supplementation and a multidomain (physical activity, cognitive training, and nutritional advice), alone or in combination, compared with placebo, on muscle strength. We also hypothesized that ω3-PUFA supplementation resulted in additional benefit in participants with a low docosahexaenoic acid (DHA)/eicos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 25 publications
2
57
1
1
Order By: Relevance
“…However, we should note that the reduction observed in TUG (1.7 s, 8%) was not statistically significant, in contrast with a previous study that found a smaller but significant reduction in TUG time (0.5 s, 7%) [30]. Moreover, the same study along with others did not find any effect of supplementation on handgrip strength, similar to the present study [28,29]. In contrast, Smith et al reported that 6 months supplementation with 1.86 g/d EPA and 1.50 g/d DHA in healthy older adults led to significant beneficial effects on handgrip strength, and upper-and lower-body 1-RM muscle strength [27].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…However, we should note that the reduction observed in TUG (1.7 s, 8%) was not statistically significant, in contrast with a previous study that found a smaller but significant reduction in TUG time (0.5 s, 7%) [30]. Moreover, the same study along with others did not find any effect of supplementation on handgrip strength, similar to the present study [28,29]. In contrast, Smith et al reported that 6 months supplementation with 1.86 g/d EPA and 1.50 g/d DHA in healthy older adults led to significant beneficial effects on handgrip strength, and upper-and lower-body 1-RM muscle strength [27].…”
Section: Discussionsupporting
confidence: 70%
“…In the last decade, there have been numerous studies demonstrating a positive impact of EPA and DHA supplementation on skeletal muscle strength and mass, even though this was not confirmed in other studies [25][26][27][28][29]. However, only few studies have examined the effect of omega-3 fatty acid supplementation on the physical performance of elderly people [27][28][29][30][31]. Nevertheless, based on these limited data of various doses and supplementation duration, there is conflicting evidence as to whether omega-3 alone or in combination with omega-6 supplementation could confer a beneficial effect on muscle function in older adults as a monotherapy and without an exercise component.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, 12 weeks supplementation with 440 mg/d DHA and 660 mg/d EPA had no effect on muscle mass or handgrip strength in community-dwelling older people (mean age 74.6 ± 8.0 years) [117]. In another study, 800 mg/d DHA and 225 mg/d EPA in combination with physical exercise, cognitive training and nutritional counseling had no effect on different measures of muscle strength in older people [118]. Based on the evidence from these trials, doses of 3000 mg/d of DHA plus EPA or more (with preferably more than 800 mg/d EPA) may be required for positive effects on physical performance in older adults [114,116] as lower doses have not had an effect [117,118].…”
Section: Omega-3 Lcpufas and Sarcopenia And Frailty In Older Peoplementioning
confidence: 94%
“…There are other multidomain interventional studies in individuals with cognitive impairment or AD that have been completed (Nousia et al, 2018;Rolland, Barreto, Maltais, Guyonnet, Cantet, Andrieu, & Vellas, 2019;Vellas et al, 2014)…”
Section: Tr Ans L Ating Epidemiolog Ic Al Obs Ervati On S Into P Otmentioning
confidence: 99%